Regenerating the teacher in a reflective space: rethinking the capstone experience at the graduate level. Issue 1 (1st January 2022) - Fraser, Mark; Wotring, Anthony
ABSTRACT: Capstone experiences function as a process in which students consolidate knowledge and skills throughout their degree programme and apply this understanding towards real-world contexts. This process is most often understood, in undergraduate programmes, as a transformation of identity, moving from "student" to "professional". However, for English teaching students at the graduate level, capstone experiences deepen existing professional knowledge and expertise. This process of self-assessment and reflection on teaching can transform and regenerate these experienced English language teachers and their teaching practices. Aiming to explore the value of graduate level capstone experiences in just these regenerative and transformative processes, this study employs a symbolic interactionist framework in analysing data collected from semi-structured interviews utilising a narrative frame approach with a group of experienced Japanese English teachers who have recently completed graduate capstones and returned to their teaching roles. Perceiving capstone experiences as objects through which these graduate students view their developing professional identities, the findings reveal that the reflective space afforded to students through the capstone enabled the students to discern a junction between theoretical principles from graduate courses and practical application. A discussion centring on the implications of graduate capstone experiences for teachers is given.